SMART VILLAGE GOVERNANCE THROUGH THE VILLAGE INFORMATION SYSTEM IN TUBAN REGENCY - Iswanto, Denny (Universitas Negeri Yogyakarta, 2022)
The rapid use of information technology (IT) in all aspects of life from government to the general public has encouraged this local government to integrate city elements to support information technology-based urban life or can be called a smart city. In line with the use of this concept, in the context of a smaller government, namely the village, the concept of a technology-based smart village or commonly referred to as a smart village has been applied. Indicators or basic elements of the smart village concept by looking at the indicators used in the smart city concept which are adapted to be more suitable for implementation in village government into Smart Governance, Smart Technology, Smart Resources, Smart Village Services, Smart Living, and Smart Tourism. This research uses descriptive analysis research method and combined with SWOT analysis method. The results showed that the application of the smart village concept in Tuban Regency did not have a previously designed development model. The implementation of smart villages is only focused on the development of administrative services in the form of the use of information technology which is only one indicator of the implementation of smart villages, but for other indicator elements it is still far from the general concept of what the actual implementation of smart villages is, so that various improvements are still needed, including the application of the development model. smart village, sustainable improvement of village information systems for the sake of ongoing public accountability in providing services to the community.